Going back to my roots : a critical understanding of the interplay between Christian faith and Shona tradition in the quest to find meaning within the HIV pandemic - Tamirepi, Farirai (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MTh (Practical Theology and Missiology))--University of Stellenbosch, 2011.